Quadratic Harmony


The roots of the equation $X^2 + 3X - 1 = 0$ are also the roots of the quadratic equation $X^4 + aX^2 + bX + c = 0$. Find the value of $a + b + 4c$.


Source: BdMO 2017 National Secondary P3


Proof Based Problems  


  1 Upvote                    1 Downvote


Solution

Disclaimer: The solutions we've shared are just one exciting approach, and there are surely many other wonderful methods out there. We’d love to hear your alternative solutions in the community thread below, so let's keep the creativity flowing!

This can be done using Vieta's Theorem (Described Below)


Let the solution to $x^2+3x-1$ be $k,l$. Here,

$k+l=-3$ and $kl=-1$

Other than $k,l$ there are 2 more solutions to the equation $x^4+ax^2+bx+c$, say $m,n$. 

Here,

$k+l+m+n=0 \implies m+n=-k-l=3$


$a=kl+mn+km+lm+kn+ln$

$\implies a=mn+kl+(m+n)(k+l)$

$\implies a=mn-1+3(-3)$

$\implies a=mn-10$


$-b=klm+kln+kmn+lmn$

$\implies b=kl(m+n)+mn(k+l)$

$\implies b=3(-1)-3mn$ 

$\implies b=3+3mn$


$4c=4klmn=-4mn$

So, $a+b+4c=mn-10+3mn+3-4mn=-7$


Vieta's Theorem:

Define a polynomial, $p$ as

\[p(x) = \sum_{i=0}^n c_ix^i\]

that has roots $a_1,~a_2,~a_3,~...,~a_n$. Vieta's theorem states that,

\[\sum_{i}a_i = -\frac{c_{n-1}}{c_n}\]

\[\sum_{i>j}a_ia_j = \frac{c_{n-2}}{c_n}\]

\[\sum_{i>j>k}a_ia_j = -\frac{c_{n-3}}{c_n}\]

\[\vdots\]

\[a_1a_2...a_n = (-1)^n\frac{c_0}{c_n}\]

Here, the sign alternates between positive and negative and the number of roots in each term keeps increasing. To be specific,

\[\sum_{m_1>m_2>...>m_k}a_{m_1}a_{m_2}...a_{m_k} = (-1)^k\frac{c_k}{c_n}\]

This is a proof based problem added for learning purposes and does not accept submissions.

You can view the solution by clicking on the solution tab.